Decentralizing Spending More Than Revenue : Does it Hurt Fiscal Performance? - Eyraud, Luc.; Lusinyan, Lusine (Washington, D.C. : International Monetary Fund, 2011)
In many countries the decentralization of spending responsibilities has outpaced the decentralization of revenue powers. Sub-national governments have then to rely on transfers from the center and borrowing to finance their spending. When this occurs, we find that the overall fiscal deficit tends to increase. This result is based on cross-country econometric evidence from OECD countries, and is particularly strong in the presence of regional disparities. Fiscal discipline can be strengthened by ensuring that sub-national taxing powers are adequate to meet spending obligations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet